Knockout of phytoene desaturase gene using CRISPR/Cas9 in highbush blueberry - Vaia, Giuseppe; Pavese, Vera; Moglia, Andrea; Cristofori, Valerio; Silvestri, Cristian (Frontiers in Plant Science, 2022)
Among the New Plant Breeding Techniques (NPBTs), the CRISPR/Cas9 system represents a useful tool for target gene editing, improving the traits of the plants rapidly. This technology allows targeting of one or more sequences simultaneously, as well as introducing new genetic variations by homology-directed recombination. However, the technology of CRISPR/Cas9 remains a challenge for polyploid species, since all the different alleles for which the mutation is required must be simultaneously targeted. In this work we describe improved protocols adapting the CRISPR/Cas9 system to highbush blueberry (Vaccinium corymbosum L.), using Agrobacterium-mediated transformation. As a proof of concept, we targeted the gene encoding for phytoene desaturase, whose mutation disrupts chlorophyll biosynthesis allowing for the visual assessment of knockout efficiency. Leaf explants of in vitro-cultured blueberry cv. Berkeley have been transformed with a CRISPR/Cas9 construct containing two guide RNAs (gRNA1 and gRNA2) targeting two conserved gene regions of pds and subsequently maintained on a selection medium enriched with kanamycin. After 4 weeks in culture on selection medium, the kanamycin-resistant lines were isolated, and the genotyping of these lines through Sanger sequencing revealed successful gene editing. Some of mutant shoot lines included albino phenotypes, even if the editing efficiencies were quite low for both gRNAs, ranging between 2.1 and 9.6% for gRNA1 and 3.0 and 23.8 for gRNA2. This study represents a further improvement in the use of CRISPR/Cas9 system in Vaccinium corymbosum L., opening the way to the breeding mediated by biotechnological approaches.